Sobre los dos modelos del espacio en las lenguas eslavas - Trifonova, I. (Eslavística Complutense, 2003)
The article study the structure of the language category of Space, the indispensability of spatial markers for Slavonic and the development, in the Bulgarian language, of the old specific Slavic group of verbs of motion, determinate vs indeterminate verbs. It was established that the “visual” semantic model of verbs of motion existing even today in synthetic Slavonic languages, was replaced, in the analytical Bulgarian language, by a “relational’ semantic model close to the spatial model of Roman languages. An opinion was expressed that the changes in the Bulgarian language which are directly related to its analytical typological characteristics should be viewed as a consequence of “common constants of language development’.